Pamhinta X mga nagbabagang sanaysay - Cano, Louie (New Manila, Quezon City Milflores Publishing, 2010)
Collection of hilarious and insightful essays in Filipino on gay life in the Philippines.
Keywords: Philippine essays -- Collections; Gays -- Philippines -- Humor; Marginality, Social -- Philippines